DEVELOPING EXTENSIVE READING STRATEGIES: A Case Study of Ten Indonesian EFL Learners - Rudi Haryono (Prodi Pendidikan Bahasa Inggris, STKIP Muhammadiyah Bogor, 2019)
This study investigates how extensive reading strategies affect tertiary level EFL students’ English reading attitudes, reading comprehension and vocabulary acquisition. A case study of ten Indonesian EFL learners at STKIP Muhammadiyah Bogor Teacher Training Institute who followed an extensive reading program for 12 weeks is presented. Students’ attitudes to the extensive reading strategies implemented were collected using qualitative data using documentation and interviews. Factors affecting motivation to read, such as time management, interest level and ease of reading material will be discussed. The study showed that the proficiency level of Indonesian EFL students in extensive reading is particularly affected by time management and the appropriateness of the level of reading materials. Students responded positively to extensive reading for a variety of reasons and extensive reading can motivate them to read more widely in English. The findings support Day and Bamford’s (2002) ten principles for extensive reading.